2005
DOI: 10.4161/cc.4.10.2077
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Inactivates the G0/G1-APC/C Ubiquitin Ligase by Cdh1 Dissociation

Abstract: The anaphase promoting complex/cyclosome (APC/C) is an E3 ubiquitin ligase that targets regulators of the cell division cycle for degradation by the 26S proteasome. Discovered as a key regulator of mitosis, the APC/C has more recently been recognized to also play a limiting role in the control of G(0) maintenance, G(1)/S-transition and DNA-replication. Human cytomegalovirus (HCMV) has been shown to interfere with cell cycle regulation at different levels. It can induce an S phase-prone proliferation program in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 38 publications
4
47
1
Order By: Relevance
“…We and others have found that, upon HCMV infection, the APC4 and APC5 subunits are degraded, the TPR subunits dissociate from the catalytic core and Cdh1, Cdh1 is hyperphosphorylated, and APC/C substrates accumulate (5,8,9). We also demonstrated that the viral kinase UL97 is capable of phosphorylating the APC/C coactivator Cdh1 on several sites, but in the context of infection, UL97 is not required for APC/C inactivation and disassembly (10).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…We and others have found that, upon HCMV infection, the APC4 and APC5 subunits are degraded, the TPR subunits dissociate from the catalytic core and Cdh1, Cdh1 is hyperphosphorylated, and APC/C substrates accumulate (5,8,9). We also demonstrated that the viral kinase UL97 is capable of phosphorylating the APC/C coactivator Cdh1 on several sites, but in the context of infection, UL97 is not required for APC/C inactivation and disassembly (10).…”
mentioning
confidence: 73%
“…Early in infection, the virus causes a stimulation of resting cells into the cell cycle and subsequent arrest at the G 1 /S border (1)(2)(3). The infection inhibits host DNA replication, affects cyclin levels (4), prevents host DNA replication licensing (5)(6)(7), and inhibits the anaphase-promoting complex/cyclosome (APC/C) (8)(9)(10).…”
mentioning
confidence: 99%
“…22), like the CAV protein Apoptin 23 and HCMV. 24 These results led us to hypothesize that E2 could induce abnormal mitoses through such a mechanism. As APC cellular inhibitors act by direct binding to Cdh1 or Cdc20, we investigated whether E2 from high-risk HPVs could interact with these two proteins.…”
Section: High-risk Hpv E2 Proteins Block Cells In G 2 /Mmentioning
confidence: 99%
“…Having shown that MCMV, unlike HCMV, fails to be negatively regulated by cyclin A2-CDK, we asked whether this difference may also be reflected at the level of virus-mediated regulation of cyclin A2-CDK activity during the course of lytic infection. To address this point, we used an approach that has been successfully employed in a number of studies to investigate the influence of HCMV on cyclin-dependent kinases and other cell cycle-related activities (5,28,71,72,75). The main principle of this approach is to infect cells (mostly nontransformed fibroblasts) that have been synchronized in G 0 /G 1 by growth factor deprivation or contact inhibition.…”
Section: Cyclin A2 Interferes With Hcmv Gene Expression In a Cdk-depementioning
confidence: 99%